BEYOND HIGH SCORES: EVALUATING ITEM DIFFICULTY AND MEASUREMENT SENSITIVITY IN BASIC NUMERACY ASSESSMENT - Laela Fauziah; Rufi’i Rufi’i; Sabariah Sabariah (Jurnal Penelitian : Politeknik Penerbangan Surabaya, 2026)
Assessment of basic numeracy is essential for identifying students' foundational mathematical competence and for supporting instructional decisions. However, very high test scores may conceal limited measurement sensitivity when an instrument contains many low-difficulty items. This study examined an existing 25-item basic numeracy assessment by interpreting highly concentrated score distributions and proportion-correct values (p-values) as preliminary indicators of item difficulty. A descriptive quantitative approach was applied to data from 35 participants. Because the available dataset did not support formal reliability estimation, item discrimination indices, distractor analysis, or IRT/CDM modelling, the analysis was limited to total-score distribution, item-level proportion-correct values, and documentary review of item explanations. Results showed strong upper-end score concentration: scores ranged from 19 to 25 (M = 23.6, SD = 1.83), and 51.4% of participants achieved the maximum score. Items 11, 18, and 19 were answered correctly by all participants, whereas Items 24 and 10 produced the lowest correct-response rates but remained easy overall (85.7% and 88.6%). Item 17 was flagged for possible ambiguity in the answer explanation. The findings indicate that the instrument functions adequately as a baseline mastery check but has limited capacity to differentiate higher-performing students. The study contributes practical evidence for revising classroom-based numeracy instruments through more balanced item difficulty, clearer keying logic, and future validation using larger samples and stronger psychometric evidence.